2020
DOI: 10.1186/s12890-020-01317-1
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between MMP2 expression in lung cancer tissues and clinical parameters: a retrospective clinical analysis

Abstract: Background Matrix metalloproteinase 2 (MMP2) has been found to be related to malignant tumors; the aim of this study was to investigate the correlation between MMP2 expression in lung cancer tissues and clinical parameters of lung cancer. Methods The expression of MMP2 in lung cancer tissues and in adjacent non-malignant tissues was tested by immunohistochemistry. The correlation between the expression of MMP2 and clinical parameters of lung cancer was analyzed by Kaplan-Meier curve and multiple regression a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 26 publications
1
39
0
Order By: Relevance
“…MMP9 expression was reported to increase with tumor size and be significantly higher in metastatic NSCLC cases than in cases without metastasis [26]. Similarly, MMP2 expression in lung cancer tissues was shown to be higher than that found in normal tissues and suggested to be related to the development of lung cancer [29].…”
Section: Introductionmentioning
confidence: 99%
“…MMP9 expression was reported to increase with tumor size and be significantly higher in metastatic NSCLC cases than in cases without metastasis [26]. Similarly, MMP2 expression in lung cancer tissues was shown to be higher than that found in normal tissues and suggested to be related to the development of lung cancer [29].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we found that paclitaxel statistically significantly decreased the expression of EGF receptors in different lung cancer cells. Although paclitaxel can suppress the EGFR signaling pathways in different cancer cells most probably via matrix metalloproteinases [ 85 , 86 , 87 , 88 ], a direct suppression of EGF receptors, in our knowledge, was not previously reported. In our studies, paclitaxel treatment reduced only about 10–15% expression of the EGFR protein when compared to the vehicle-treated cells.…”
Section: Discussionmentioning
confidence: 97%
“…Invasion-associated proteins MMP-2 (72 kDa gelatinase A) and MMP-9 (92 kDa gelatinase B) promote tumor invasion and metastasis through disruption of extracellular matrix (ECM) and induction of epithelial-mesenchymal transition (EMT) (27,28). High expressions of both MMP-2 and MMP-9 as unfavorable prognostic predictors were correlated with lymph node metastasis and poor prognosis in NSCLC patients (29,30). Our results demonstrated that the combination of regorafenib and cisplatin not only significantly reduced the number of migration and invasion cells, but also effectively abolished protein levels of both MMP-2 and MMP-9 compared to regorafenib or cisplatin monotherapy (Figure 3).…”
Section: Discussionmentioning
confidence: 99%